2021
DOI: 10.1080/07853890.2021.1903072
|View full text |Cite
|
Sign up to set email alerts
|

Changes of epicardial fat thickness after laparoscopic sleeve gastrectomy: a prospective study

Abstract: Purpose Epicardial fat thickness is an interesting parameter of early atherosclerosis. We prospectively assessed whether weight loss following laparoscopic sleeve gastrectomy (LSG) leads to a significant reduction in the epicardial fat thickness (EFT) and the correlation between the decline in the epicardial fat thickness with other clinical parameters. Methods A prospective analysis of 98 cases that were scheduled to undergo LSG and followed up for 12 months was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Also important is proper hydration and ensuring good physical activity with the aerobic activity of medium intensity for 30-45 minutes most days (15). In agreement with these observations, prior retrospective research found a decrease in "epicardial fat thickness" after "bariatric surgery", which was related to "the degree of weight loss" (16). A similar conclusion was made by Gaborit et al (17) in a somewhat more latest study.…”
Section: Discussionsupporting
confidence: 66%
“…Also important is proper hydration and ensuring good physical activity with the aerobic activity of medium intensity for 30-45 minutes most days (15). In agreement with these observations, prior retrospective research found a decrease in "epicardial fat thickness" after "bariatric surgery", which was related to "the degree of weight loss" (16). A similar conclusion was made by Gaborit et al (17) in a somewhat more latest study.…”
Section: Discussionsupporting
confidence: 66%
“…These alterations encompass an upsurge in the volume of epicardial adipose tissue and changes in the size and morphology of adipocytes (Iacobellis, 2021). Age-related metabolic adjustments, namely insulin resistance and modified lipid metabolism, can contribute to the expansion of epicardial adipose tissue (Salman et al, 2021). These shifts may impel a pro-inflammatory state within the adipose tissue, which could lead to the release of inflammatory mediators and an increased susceptibility to cardiovascular diseases, including atrial fibrillation (Guglielmi and Sbraccia, 2017).…”
Section: Age-related Changesmentioning
confidence: 99%
“…Multiple studies have explored the effect of bariatric surgery, including sleeve gastrectomy and Roux‐en‐Y gastric bypass, on reducing EAT amount. 131 , 139 , 150 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 Most of them demonstrated a significant association between bariatric surgery and reduction in EAT amount; only one of these studies has reported a negative result (nonsignificant change in EAT amount), which might be due to a relatively shorter follow‐up duration (3 months). 162 According to a meta‐analysis, sleeve gastrectomy is more effective in decreasing EAT than Roux‐en‐Y gastric bypass.…”
Section: Exploration Of Targeting Eat As a Therapeutic Strategymentioning
confidence: 99%